Enhancing Cellulose-Gelatin Film Properties for Wound Dressings Application: The Role of Ultrasonic-Assisted Pretreatment - Shafira Nur Adiningsih; Sekar Tri Wulan Amelia; Ni Made Intan Putri Suari; Heru Setyawan; Widiyastuti, Widiyastuti; Nurtono, Tantular (Chemistry Department, The University of Brawijaya, 2026)
This study aims to enhance the cellulose-gelatin film properties using ultrasonic-assisted pretreatment for wound dressing applications. The film is made from cellulose isolated from avocado seed waste, composited with gelatin, and applied citric acid as a crosslinker and antimicrobial agent. The main factor that affects the performance of cellulose in films was dispersion of cellulose within the composite material. To improve cellulose dispersion, cellulose was pretreated using ultrasonic-assisted methods, its effects on film’s properties were investigated and compared with no ultrasonic pretreated cellulose. Scanning electron microscopy revealed more even dispersion in ultrasonic pretreated samples, further confirmed by their chemical bonds analysis. These improvements significantly enhanced the mechanical properties of the composite film, increasing the tensile strength from 0.099 MPa to 0.988 MPa and the percent elongation from 77 % to 106 %. Moreover, films with ultrasonic pretreated cellulose exhibited resilient swelling behavior, indicating better resilience in aqueous environment. Additionally, films revealed antibacterial activity against gram-positive and gram-negative bacteria, which has inhibition zone against Escherichia coli for CF-nSON and CF-SON are 39 mm and 35, mm respectively. As the inhibition zone against Staphylococcus auerus for CF-nSON and CF-SON are 33 mm and 26.3 mm, respectively. These results are pointing out their performance as wound dressing.